2018
DOI: 10.1007/s00701-018-3520-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal brain activation changes related to electrophysiological findings in patients with cervical spondylotic myelopathy before and after spinal cord decompression: an fMRI study

Abstract: Abnormal corticospinal MEP findings in cervical spondylotic myelopathy were associated with differences in brain activation, which further increased after spinal cord decompression and did not resolve within 12-month follow-up. In summary, surgery may come too late for those patients with abnormal MEP to recover completely despite their mild clinical signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…A few years ago it was shown that there were electrophysiological abnormalities even very early after symptom onset in DCM, despite minimal disability. 5 And that abnormal corticospinal MEP changes correlated with fMRI increased brain activation. This supported the hypothesis that brain reorganisation does happen, with positive neuronal plasticity, but it did not help identify at which point surgical intervention might be optimal.…”
mentioning
confidence: 95%
“…A few years ago it was shown that there were electrophysiological abnormalities even very early after symptom onset in DCM, despite minimal disability. 5 And that abnormal corticospinal MEP changes correlated with fMRI increased brain activation. This supported the hypothesis that brain reorganisation does happen, with positive neuronal plasticity, but it did not help identify at which point surgical intervention might be optimal.…”
mentioning
confidence: 95%
“…Functional MRI (fMRI) measures oscillations in neuronal activity utilizing either T2*-w sequence sensitive to local magnetic field inhomogeneities related to blood oxygenation level-dependent effect or arterial spin labelling sequences based on arterial water as an endogenous tracer to measure cerebral blood flow [116]. Brain fMRI studies indeed revealed remote changes in activations of motor areas during finger-tapping tasks between DCM patients and HC [11,117], alterations of sensorimotor network in resting-state fMRI in DCM patients [118], the relationship between severity of compression in DCM patients and activation volume in the motor cortex [119], and differences in brain activations in DCM patients with abnormal motor evoked potentials [120] suggesting that SC compression causes secondary brain changes. Spinal cord resting-state fMRI then showed neuronal activity changes in GM horns in 18 DCM patients relative to 25 HC and association of severity of myelopathy with neuronal activity response [121], however, no study has been performed in NMDC [122] yet further emphasizing the need to add fMRI in multimodal SC protocols.…”
Section: Functional Mrimentioning
confidence: 99%
“…Functional MRI (fMRI) measures the oscillations in neuronal activity by either a T2*-w sequence, sensitive to local magnetic field inhomogeneities related to blood oxygenation level-dependent effect, or arterial spin labeling sequences that utilize arterial blood as an endogenous tracer to measure cerebral blood flow [95]. Brain fMRI studies, indeed, revealed: remote changes in the activations of motor areas during finger-tapping tasks between DCM patients and HC [9,96], alterations of the sensorimotor network in restingstate fMRI in DCM patients [97], the relationship between severity of compression in DCM patients and activation volume in the motor cortex [98], and differences in brain activations in DCM patients with abnormal motor evoked potentials [99], suggesting that DSCC causes secondary brain changes. A single SC resting-state fMRI study showed neuronal activity changes in the GM horns of 18 DCM patients, relative to 25 HC, as well as an association of severity of myelopathy with neuronal activity response [100].…”
Section: Functional Mrimentioning
confidence: 99%